Effectiveness of Egg Intervention on Linear Growth in Stunting Children: A Systematic Review - Rice Mandowa; Kadek Ayu Erika; Syahrul Syahrul (GLOBAL HEALTH SCIENCE GROUP, 2025)
Complementary feeding of eggs to children is one of the strategies to improve growth in stunted children. It is necessary to develop egg complementary feeding interventions based on local food availability. Whether egg complementary feeding interventions can improve growth in children with growth retardation. Our aim in this systematic review was to assess the effect of egg or complementary feeding interventions on improving linear growth in stunted children. Electronic databases were used to systematically search for articles reviewing the literature using PubMed, Cochrane and base, and garuda databases. The research question was based on PICO. A total of 969 articles were found and only six articles met the inclusion criteria and were published within 10 years (2011-2021). All articles were RCTs and in children aged 6 months and 24 months with growth retardation. From the critical appraisal of the included articles, egg intervention significantly improved linear growth in children with growth retardation. An approach was adopted to identify several well-designed trials that examined the effect of egg interventions on growth. This intervention should be provided as holistic pediatric nutrition.